Colorectal Cancer: The Impact of Smoking and Alcohol on Risk in West Nusa Tenggara, Treatment, and Prevention - Arif Zuhan; Syakir, Syahda Aqila (Jurnal Biologi Tropis, 2024)
: Colorectal cancer (CRC) is the third most common cancer globally and the second leading cause of cancer-related mortality. It results from complex interactions between genetic, environmental, and lifestyle factors, with smoking and alcohol consumption being significant contributors. This study focuses on the correlation between smoking and alcohol consumption with CRC incidence in West Nusa Tenggara (NTB), a province in Indonesia known for its high smoking prevalence (32.79%) and alcohol consumption rate (1.6%). A literature review methodology was employed, systematically collecting data from PubMed, ScienceDirect, Cochrane Library, Google Scholar, and ProQuest using keywords such as "colorectal cancer," "risk factors," "smoking," "alcohol," "management," and "prevention." A total of 35 articles published between 2007 and 2024 were analyzed to provide a comprehensive synthesis of CRC risk factors, management approaches, and prevention strategies. The findings reveal a strong association between smoking and CRC risk, particularly among middle-aged males, while alcohol amplifies the risk synergistically. Despite limited alcohol prevalence, its impact remains substantial. The study emphasizes the importance of targeted public health interventions in NTB, integrating lifestyle modification campaigns and routine screenings to mitigate CRC risks and improve health outcomes in high-risk communities.